1994
DOI: 10.1073/pnas.91.8.3329
|View full text |Cite
|
Sign up to set email alerts
|

Cell-adhesion-disrupting action of interleukin 6 in human ductal breast carcinoma cells.

Abstract: Recombinant baculovirus-derived interleukin 6 (IL-6) disrupts the attachment of human ductal breast carcinoma subline ZR-75-1-Tx cells to neighbors and the substratum in culture without inhibiting the proliferation ofthe cells. The nonadherent cells lack pseudopodia and do not translocate directionally. These findings stand in contrast to the earlier observations in the Ro subline of ZR-75-1 cells in which 11-6 induces cell-cell separation without detachment of the cells from the substratum, with the cells dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 18 publications
1
37
0
Order By: Relevance
“…First, our results indicate that standard meanfield models, such as the logistic equation, might not be the most appropriate model to apply to a given data set. This is of particular interest given that many experimental observations of collective cell behaviour indicate that cell populations often involve significant clustering (Hackett-Jones et al 2012;Lah and Key 2012;Tamm et al 1994). Second, although standard mean-field models can be inappropriate for describing processes involving clustering or patchy dynamics, these models can still be calibrated to patchy or clustered data sets to produce a good match to the observed data.…”
Section: Discussionmentioning
confidence: 99%
“…First, our results indicate that standard meanfield models, such as the logistic equation, might not be the most appropriate model to apply to a given data set. This is of particular interest given that many experimental observations of collective cell behaviour indicate that cell populations often involve significant clustering (Hackett-Jones et al 2012;Lah and Key 2012;Tamm et al 1994). Second, although standard mean-field models can be inappropriate for describing processes involving clustering or patchy dynamics, these models can still be calibrated to patchy or clustered data sets to produce a good match to the observed data.…”
Section: Discussionmentioning
confidence: 99%
“…Second, inflammatory cytokines can provoke phenotypic changes that are independent of the immune system in nearby cells. For example, IL-6 and IL-8 can stimulate angiogenesis, disrupt cell-cell communication, impede macrophage function, induce innate immune responses, and promote epithelial and endothelial cell migration and invasion (73)(74)(75)(76)(77)(78)(79).…”
Section: Cellular Senescencementioning
confidence: 99%
“…It has also been demonstrated that mechanical stress can trigger certain responses in TM cells, including cytoskeletal changes, induction of gene expression, and activation of regulatory pathways [13][14][15][16][17][18][19][20][21] One of the reported responses to increased IOP in perfused human anterior segments observed by gene array analysis is an increase in interleukin-6 (IL-6) mRNA [16]. IL-6 is well known to increase the permeability of vascular endothelium through effects on the paracellular pathway, induction of matrix metalloproteinases (MMPs), and vesicular trafficking [22][23][24]. This array of effects mediated by IL-6 suggests that this cytokine could affect aqueous humor outflow resistance in the outflow pathway by increasing the permeability of the inner wall cells of SC [25] and/or reducing extracellular matrix (ECM) resistance at the level of the juxtacanalicular tissue (JCT) [5,[26][27][28][29].…”
mentioning
confidence: 99%
“…IL-6 is well known to increase the permeability of vascular endothelium through effects on the paracellular pathway, induction of matrix metalloproteinases (MMPs), and vesicular trafficking [22][23][24]. This array of effects mediated by IL-6 suggests that this cytokine could affect aqueous humor outflow resistance in the outflow pathway by increasing the permeability of the inner wall cells of SC [25] and/or reducing extracellular matrix (ECM) resistance at the level of the juxtacanalicular tissue (JCT) [5,[26][27][28][29].…”
mentioning
confidence: 99%